2018
DOI: 10.1097/md.0000000000012274
|View full text |Cite
|
Sign up to set email alerts
|

Unusual variant of distal biceps femoris muscle associated with common peroneal entrapment neuropathy

Abstract: Rationale:The anatomical variant of the distal biceps femoris muscle with regard to common peroneal nerve entrapment neuropathy (CPNe) was suggested through magnetic resonance images (MRI) study.Patient concerns:An unusual variant of distal biceps femoris muscle was observed in 78 years old male cadaver.Diagnoses:The short head of biceps femoris muscle (SHBFM) was extended more distal and posteriorly.Intervention:The popliteal area was dissected at knee joint level in a cadaveric limb.Outcomes:Common peroeal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Typically, the CPN arises from the sciatic nerve at the upper level of the popliteal fossa and runs obliquely along the medial side of the BFM and then superficial to the LGCM ( Figure 2 ). The authors reported a cadaveric case with variant of distal BFM associated with CPNe [ 16 ]. In cadavers with variation, the tibial nerve was found at the popliteal fossa, but the CPN was not observed at its medial margin.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, the CPN arises from the sciatic nerve at the upper level of the popliteal fossa and runs obliquely along the medial side of the BFM and then superficial to the LGCM ( Figure 2 ). The authors reported a cadaveric case with variant of distal BFM associated with CPNe [ 16 ]. In cadavers with variation, the tibial nerve was found at the popliteal fossa, but the CPN was not observed at its medial margin.…”
Section: Resultsmentioning
confidence: 99%
“…Some patients manifested paresthesia [76]. It is important to consider that there were rare cases of asymptomatic patients who presented the muscular variant [74,89].…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…The deep peroneal nerve runs with the anterior tibial vessels over the interosseous membrane into the anterior compartment of the leg and then over the ankle to the dorsum of the foot. It supplies all of the muscles of the anterior compartment for dorsiflexion of the toe and ankle as well as providing a cutaneous supply to the area between the 1st and 2nd toes 24,28,30,35,37) .…”
Section: Function: Motor and Sensorymentioning
confidence: 99%